Spine surgery techniques, somplication avoidance, and management (Elsevier, 2012)
Make the best use of the latest techniques with step-by-step guidance from Spine Surgery. Edited by Edward C. Benzel, this best-selling neurosurgery reference explores the full spectrum of surgical techniques used in spine surgery and delivers the comprehensive, cutting-edge guidance you need to achieve successful outcomes. Glean essential, up-to-date information in one comprehensive reference that explores the full spectrum of techniques used in spine surgery. Hone your surgical skills and technique with intraoperative videos and more than 800 outstanding illustrations demonstrating each technique step by step.